Comprehensive design of a 100-kilowatt solar power plant with bifacial technology in PVsyst for Arak, Iran - Mohammad Parhamfar; Alireza Zabihi (Solar Energy Advances)
Modeling a PV power plant using PVsyst software requires careful attention in selecting and adjusting the bi-facial factor as it can significantly impact the performance of the modeled system or power plant. In designing solar power plants, we must consider important details. This article explores the design of a 100-kW rooftop solar power plant, addressing challenges and selecting the best design, particularly focusing on the impact of bi-facial coefficients. One of the challenges is accurately assessing the amount of radiation received from the rear of the panels and optimizing the row spacing to prevent shading. Another challenge is determining the effective installation angles and the height of the panels above the ground to enhance bi-facial efficiency. Neglecting to properly configure this factor can lead to incorrect energy yield estimates and negatively affect the economic analysis of the designed project. The main objective is to create an appropriate design for bi-facial PV systems in PVsyst by considering several obstacles. These challenges include field segment shading, solar energy availability in different months, nearby shading, roof configuration and wiring, cable design, grounding system, protection system calculation, risk assessment, lighting, and installation of lightning rods for shadow measurement. Various software, such as AutoCAD, PVsyst, ETAP, PVLPC, Helioscope and Volta, were utilized in this study. Moreover, the economic analysis in this study is conducted using RETScreen, a widely recognized software tool designed for evaluating the financial viability and performance of renewable energy and energy efficiency projects. This paper is based on a real project implemented in Arak, Iran. Furthermore, this paper explores incorporating climatic and environmental impacts into PVsyst software for accurate power plant performance prediction, providing a practical example for designing a 100-kilowatt plant.